A Protracted Course of COVID19 Infection in a Metastatic Breast Cancer Patient During CDK4/6 Inhibitor Therapy - Grinshpun, Albert; Merlet, Irit; Fruchtman, Hila; Nachman, Dean (Frontiers in Oncology, 2020)
We describe the first case report of a patient with COVID19 infection and metastatic breast cancer, while on systemic therapy with a CDK4/6 inhibitor. The patient had unique disease course, characterized with delayed symptomatology. The case highlights novel findings and stress careful and extended follow-up during COVID19 infection in patients taking biologic therapies affecting the immune system.